Optimal timing of surgery for patients with infective endocarditis. (3rd May 2023) - Manikantan, P; Tao, M; Despotidis, G; Alkhalil, A; Parikh, P; Pyo, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Infective endocarditis (IE) is a disease associated with high risk of morbidity and mortality. Recent literature suggests that surgery during index hospitalization may be performed safely without increased risk of adverse clinical outcomes. However, risk associated with specific surgical timing during index hospitalization remains unclear. Purpose: The purpose of this meta-analysis is to assess the association of early surgery with mortality in patients with IE. Methods: We performed a literature search for studies reporting an association between early surgery and study endpoints. The primary endpoint was in-hospital mortality. The secondary endpoint was long-term mortality. Early surgery was defined as surgery within 14 days of admission. The search included the following databases: Ovid MEDLINE, EMBASE, Web of Science, and Google Scholar. The search was not restricted to time or publication status. Results: A total of 15 studies with 2491 participants (900 with early surgery vs 1591 with delayed surgery) were included. The mean duration of follow-up was 33 months (ranging between 6 to 66 months). Early surgery was not associated with increased risk of in-hospital or long-term mortality compared to delayed surgery (OR 1.08, 95% CI 0.80, 1.46; P=0.63; OR 1.12, 95% CI 0.68, 1.86; P=0.65). Heterogeneity was low: Chi2 = 7.85, I2 = 0%. Subgroup analysis by time to surgery demonstrated that early surgery was not associated with increased risk of in-hospital mortality for surgeries performed within 2 days, 7 days, or 14 days of hospitalization (OR 0.87, 95% CI 0.58, 1.32; P=0.51; OR 1.06, 95% CI 0.78, 1.43; P=0.72; OR 0.51, 95% CI 0.21, 1.23; P=0.13). Heterogeneity was low: Chi2 = 4.84, I2 = 0%. Conclusions: Early surgery performed within 14 days of initial hospitalization is not associated with increased risk of in-hospital mortality or long-term mortality compared to delayed surgery.